An Evaluation of Teachers' Opinions about the Servant Leadership Behaviours of School Principals - Robert Insley; Paula Iaeger; Abdurrahman Ekinci; Halis Sakiz (ÜNİVERSİTEPARK Limited, 2016)
The aim of this study was to determine the servant leadership behaviors that were displayed, or expected to be displayed, by principals towards the teaching staff at their schools, from the teachers' perspectives. The data was collected during focus group discussion with 12 teachers who were in service in primary and secondary schools. The teachers were chosen using the snowball sampling method. The data obtained from the participants was analyzed using content analysis. When the findings were evaluated, it was determined that the principals were not qualified enough to display servant leadership behaviors. Moreover, the teachers stated that principals should display servant leadership behaviors that are oriented towards community building, sharing, empathy, active listening, humility, and altruism. In this respect, it can be suggested that principals should receive servant leadership education through instructional programs that should be developed.